GAMMA-RAY BURSTS WITHOUT MEASURED REDSHIFTS I: ENERGY ESTIMATE AND LAT BORESIGHT ANGLE DISTRIBUTION - Aimuratov, Y.K. (Academic Scientific Journal of Computer Science, 2020)
Context. With this short note we start a series of communications dedicated to the study of gammaray bursts (GRBs) without measured redshifts. Aims. We make an attempt to estimate energy of GRBs without measured distances based on population of bursts with measured redshift. Methods. We assume that there is indeed universal bimodal distribution on duration which is followed by all the events. Using data on best-fit spectral parameters from GBM GRB Catalog we calculate energy for each burst given mean redshift values for short/long distribution. Additionally, we cross-correlate GBM GRB Catalog with general GBM Trigger Catalog in order to retrieve information on LAT boresight angle at the moment of event detection. Results. We obtained estimate energy for each burst and built a distribution plot which follows the idea of bimodal distribution. A scatter plot for LAT boresight angles of short GRBs was obtained. Conclusions. The energy-based histogram follows a general pattern for short/long distribution having distinct peaks. On the other hand, LAT boresight angles for short events shows quite uniform distribution, and being an instrumental feature, therefore cannot implicitly point to some intrinsic mechanisms responsible for high-energy photons generation.